ADVANCING ARCHITECTURAL VISUALIZATION: THE IMPACT OF 3D MODELING AND RENDERING ON DESIGN COMMUNICATION - Paula Alejandra Diaz Munoz (IPHO-Journal of Advance Research in Science And Engineering, 2025)
Architectural visualization has undergone significant transformation with the integration of 3D modeling and rendering technologies, enhancing the way design concepts are communicated among stakeholders. This study investigates the impact of advanced visualization techniques on design communication, stakeholder understanding, and project efficiency. A mixed-methods research approach was adopted, involving 20 architectural design projects and 80 participants representing architects, clients, engineers, and non-technical stakeholders. The study compared traditional two-dimensional drawings with 3D modeling, high-quality rendering, and interactive walkthroughs using structured evaluation parameters including communication clarity, spatial understanding, decision-making efficiency, and stakeholder satisfaction. The results revealed substantial improvements in communication effectiveness and comprehension with advanced visualization methods. Interactive walkthroughs and high-quality renderings demonstrated the highest performance across all indicators, significantly reducing design revisions, communication errors, and approval time. Canonical Correspondence Analysis further highlighted strong relationships between visualization quality, realism, and improved communication outcomes. The findings confirm that advanced visualization technologies play a crucial role in enhancing stakeholder engagement, reducing project uncertainties, and improving architectural decision-making processes. The study concludes that integrating 3D modeling and rendering technologies into architectural workflows significantly advances design communication and project efficiency in contemporary architectural practice.